The Effects of Dollarisation to the Zimbabwean Economy (1990-2017) - Chanakira, Blessmore (Graduate School of Business (GSB), 2019)
The study aims to establish the effects of dollarisation on the Zimbabwean economy covering a period of 28 years from 1990 to 2017. The study employed Autoregressive Distributed Lag (ARDL) model to establish the short and long run relationship between dollarisation, financial performance indicators (FPIs) (Inflation, foreign direct investment, trade openness and Gross Domestic Product) and non-financial performance indicators (NFPIs) (rule of law). Annual time series data was considered under this study. In the long run dollarisation positively influences gross domestic product and trade openness and negatively influences inflation. In the short run dollarisation is significantly related to gross domestic product, trade openness and inflation. Short run results indicate that dollarisation is negatively related to gross domestic product and inflation and positively related to trade openness. Based on the findings from the empirical analysis, Zimbabwe is discouraged from de dollarizing since it requires a long-term strategy with robust policies put in place. Zimbabwe should return to full dollarisation and select the rand as an anchor currency whilst preparing to join the common monetary area. It is also recommended that Zimbabwe should put in place performance measures to measure governance indicators with emphasis on respect for property and human rights, including fighting corruption.